A case for revisiting Nodal signaling in human pluripotent stem cells. (10th May 2021) - Hayes, Kevin; Kim, Yun‐Kyo; Pera, Martin F.
Abstract: Nodal is a transforming growth factor‐β (TGF‐β) superfamily member that plays a number of critical roles in mammalian embryonic development. Nodal is essential for the support of the peri‐implantation epiblast in the mouse embryo and subsequently acts to specify mesendodermal fate at the time of gastrulation and, later, left‐right asymmetry. Maintenance of human pluripotent stem cells (hPSCs) in vitro is dependent on Nodal signaling. Because it has proven difficult to prepare a biologically active form of recombinant Nodal protein, Activin or TGFB1 are widely used as surrogates for NODAL in hPSC culture. Nonetheless, the expression of the components of an endogenous Nodal signaling pathway in hPSC provides a potential autocrine pathway for the regulation of self‐renewal in this system. Here we review recent studies that have clarified the role of Nodal signaling in pluripotent stem cell populations, highlighted spatial restrictions on Nodal signaling, and shown that Nodal functions in vivo as a heterodimer with GDF3, another TGF‐β superfamily member expressed by hPSC. We discuss the role of this pathway in the maintenance of the epiblast and hPSC in light of these new advances. Abstract : Hayes et al discuss the implications of recent advances in our understanding of Nodal signaling for the maintenance and self‐renewal of human pluripotent stem cells.